Intra-specific variation in advertisement call of Odontophrynus cordobae (Anura, Cycloramphidae): A multilevel and multifactor analysis - Grenat, Pablo Raúl (2013)
Advertisement call is a complex signal that can vary at different scales and the characterization of this variation is crucial to understand its adaptive function. In our study, we examined different factors that could influence intra and interpopulation call variation in Odontophrynus cordobae. We analyzed calls of individuals from different breeding sites across the species distribution, including a syntopic site with their related species O. americanus. Dominant frequency, pulse rate, call duration and pulses/call were the acoustic parameters that showed the lowest intra-individual variation (CV ≤ 3%). The discriminant function analysis (DFA) assigned 92% of calls to the correct individual, indicating that the advertisement calls of O. cordobae are individually distinctive. Univariate and multivariate statistical analysis showed a significant contribution of pulse rate in differentiation of populations. Interpulse interval and pulse rate showed a moderate clinal variation, even when syntopic populations were excluded from the analysis. We found no association between acoustic and linear geographical or altitudinal distances and observed an evident divergence between the syntopic population and the other populations analyzed. This result is reinforced by DFA, which showed a differentiation among syntopic and allopatric populations of O. cordobae. We discuss our results from the hypothesis of a possible character displacement influencing call properties in this species in syntopy with their related species O. americanus. However, new syntopic areas and tests of female preferences would be needed to strengthen our results.